Aberrantly Activated APOBEC3B Is Associated With Mutant p53-Driven Refractory/Relapsed Diffuse Large B-Cell Lymphoma - Zhang, Xuzhao; Wu, Zhaoxing; Hao, Yuanyuan; Yu, Teng; Li, Xian; Liang, Yun; Li, Jinfan; Huang, Liansheng; Xu, Yang; Li, Xiuzhen; Xu, Xiaohua; Wang, Weiqin; et al. (Frontiers in Immunology, 2022)
Tumor protein 53 (TP53) mutation predicts an unfavorable prognosis in diffuse large B-cell lymphoma (DLBCL), but the molecular basis for this association remains unclear. In several malignancies, the cytidine deaminase apolipoprotein B mRNA editing enzyme catalytic subunit 3B (APOBEC3B) has been reported to be associated with the TP53 G/C-to-A/T mutation. Here, we show that the frequency of this mutation was significantly higher in relapsed/refractory (R/R) than in non-R/R DLBCL, which was positively associated with the APOBEC3B expression level. APOBEC3B overexpression induced the TP53 G/C-to-A/T mutation in vitro, resulting in a phenotype similar to that of DLBCL specimens. Additionally, APOBEC3B-induced p53 mutants promoted the growth of DLBCL cells and enhanced drug resistance. These results suggest that APOBEC3B is a critical factor in mutant p53-driven R/R DLBCL and is therefore a potential therapeutic target.